Applying Precedence Rules in Executing Work for the Purpose of Balancing Assembly Lines Using Electronic Tables - Elterik, Salem; Azouza, Omar; Naser, Madi; Al-Usta, Shaima (Journal of Pure & Applied Sciences, 2024)
The issue of balancing assembly lines is one of the important activities in production and operations management because of its importance in raising the efficiency and effectiveness of assembly lines, reducing wasted time, and reducing bottlenecks that hinder the flow of production. Among the problems facing production operations is the decrease in line efficiency in addition to the presence of wasted time and the occurrence of accidents. Production bottleneck between workstations, so the goal of this paper was to balance the assembly line by following different precedence rules. A system was designed to re-arrange and balance the assembly line using the Excel program, with the aim of obtaining the best arrangement according to five ways of arranging tasks. The results showed that the priority rule for the weighted site weighing method had the highest efficiency of 88% and the lowest wasted time of 22 minutes.